2021
DOI: 10.1002/jmv.26685
|View full text |Cite
|
Sign up to set email alerts
|

Trends in acute viral gastroenteritis among children aged ≤5 years through the national surveillance system in South Korea, 2013–2019

Abstract: Acute gastroenteritis is a global public health concern. This study aimed to analyze the trend and characteristics of acute viral gastroenteritis through a national surveillance network. Enteric viruses were detected in 9510 of 31,750 (30.1%) cases assessed from 2013 to 2019 by EnterNet. The most prevalent pathogens were norovirus (15.2%) and group A rotavirus (9.7%); most infections were reported in 2017 (34.0%). Norovirus and rotavirus coinfections were the most common. Norovirus infections were prevalent am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Rotavirus and adenovirus infections are seen throughout the year. Rotavirus infection is common in many countries in winter and spring 13,14,19,22 . This study found that the rotavirus infections increased from December to April and then decreased until September.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Rotavirus and adenovirus infections are seen throughout the year. Rotavirus infection is common in many countries in winter and spring 13,14,19,22 . This study found that the rotavirus infections increased from December to April and then decreased until September.…”
Section: Discussionmentioning
confidence: 60%
“…Rotavirus infection is common in many countries in winter and spring. 13,14,19,22 This study found that the rotavirus infections increased from December to April and then decreased until September. The adenovirus infection was observed in January with the highest positive rate.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations